Description of Midwives' Compliance in Filling Out the Maternal and Child Health Book for Pregnant Women in the Indonesian Midwife Association Ranting Rambipuji Area - Puspitawati, Kurnia; Maryanti, Syiska Atik; Aby Restanty, Dian (Universitas Bondowoso, 2025)
Background: The Maternal and child health book book is a source of maternal and fetal health information used by health workers, especially midwives, as a communication medium. This book is given to every pregnant mother up to a child aged 6 years. Based on 2018 East Java Riskesdas data, 75.5% of mothers have a Maternal and child health book and 24.5% of mothers do not have a Maternal and child health book. Based on a preliminary study, most of the (30%) midwives in the Indonesian Midwife Association area of ​​the Rambipuji Community Health Center branch did comply with documentation in the Maternal and child health book. The aim of this research is to describe the compliance of midwives in filling out MCH books for pregnant women in the Indonesian Midwife Association Ranting Rambipuji area Methods: Descriptive research design with descriptive survey method. The population is 52 TPMB and the sample of 52 TPMB techniques is a saturated sample. The instruments used questionnaires and Maternal and child health book for pregnant women. Results: Some midwives are compliant in carrying out documentation in the Maternal and child health book which consists of 5 indicators, compliance rates include identity (13.5%), maternal services (0%), birth orders (5.8%), pregnancy service charts (42.3%) and weight gain graph (15.4%) Conclusion: Midwives in the Indonesian Midwife Association Rambipuji branch area do not document care in accordance with the provisions. This can be a concern for regional Indonesian Midwife Association to improve the abilities and skills of midwives in filling out MCH books by holding training